Clinical indices and local levels of inflammatory biomarkers in per‐implant health of obese and nonobese individuals. (13th December 2018) - Alasqah, Mohammed N.; Al‐Shibani, Nouf; Al‐Aali, Khulud Abdulrahman; Qutub, Osama A.; Abduljabbar, Tariq; Akram, Zohaib
Abstract: Background: Obesity seem to regulate peri‐implant health. It is proposed that peri‐implant crevicular fluid (PICF) levels of interleukin (IL)‐1β and IL‐6 are higher in obese as compared to nonobese individuals. Objective: The purpose of the present clinico‐laboratory study is to estimate and compare the clinical and radiographic indices and PICF levels of IL‐1β and IL‐6 among obese and nonobese patients. Materials and Methods: Fifty patients were divided into two groups (25 obese with ≥27.5 kg/m 2 and 25 nonobese with <27.5 kg/m 2 individuals). Clinical indices for both periodontal and peri‐implant evaluating plaque index (PI), bleeding on probing (BOP), probing depth (PD), clinical attachment level (CAL), and crestal bone loss (CBL) were recorded around teeth and implants. PICF was collected and assessed for the levels of IL‐1β and IL‐6 using enzyme‐linked immunosorbent assay. Results: A significant difference was observed in PI and BOP around natural teeth and implants in obese patients, respectively ( P < .05). CBL was found to be significantly higher among obese as compared to nonobese patients ( P = .022). Peri‐implant and periodontal PD was higher in obese as compared to nonobese but did not reach statistical significance. Levels of IL‐1β and IL‐6 were statistically significantly higher among obese patients as compared to nonobese ( P = .001). Pearson correlation analysis showed IL‐1β was positively correlated with CBL ( P = .0079), whereas IL‐6 showed positive correlation with both BOP ( P = .0019) and CBL ( P = .015) among obese patients. Conclusions: Clinical peri‐implant parameters were worse and proinflammatory biomarkers were significantly higher in obese patients compared with nonobese subjects. The findings of the present study suggests that increased proinflammatory biomarkers in PICF of obese patients may modulate peri‐implant inflammation around dental implants.